2013
DOI: 10.1002/da.22221
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymorphism in the Brain-Derived Neurotrophic Factor Gene Interacts With Stressful Life Events but Not Childhood Maltreatment in the Etiology of Depression

Abstract: The Met allele of BDNF increases the risk of a new depressive episode following a severe life event. The BDNF and the serotonin transporter gene length polymorphism (5-HTTLPR) and BDNF may contribute to depression through distinct mechanisms involving interactions with childhood and adulthood adversity respectively, which may, in combination, be responsible for a substantial proportion of depression burden in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 50 publications
(136 reference statements)
2
27
0
Order By: Relevance
“…The present study, however, is the first to document a stress sensitizing effect of the BDNF Met allele on negative affect in the context of daily stressful life events—an effect that was robust even when adjusting for other known determinants of stress reactivity, such as dysfunctional attitudes and internalizing and externalizing symptomatology. The findings thus support the construct validity of the BDNF gene–environment interaction hypothesis (Brown et al 2014). Considered more broadly, the findings add to an emerging line of research on the dynamic associations between cognitive vulnerability, molecular genetics, and emotional disorders (Gibb et al 2013), which is part of a general push toward a greater rapprochement of genetics, neuroscience, and psychology in the service of building more comprehensive, integrative explanatory models of mental and physical health (e.g., Caspi and Moffitt 2006; Kendler 2008; Slavich and Cole 2013).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present study, however, is the first to document a stress sensitizing effect of the BDNF Met allele on negative affect in the context of daily stressful life events—an effect that was robust even when adjusting for other known determinants of stress reactivity, such as dysfunctional attitudes and internalizing and externalizing symptomatology. The findings thus support the construct validity of the BDNF gene–environment interaction hypothesis (Brown et al 2014). Considered more broadly, the findings add to an emerging line of research on the dynamic associations between cognitive vulnerability, molecular genetics, and emotional disorders (Gibb et al 2013), which is part of a general push toward a greater rapprochement of genetics, neuroscience, and psychology in the service of building more comprehensive, integrative explanatory models of mental and physical health (e.g., Caspi and Moffitt 2006; Kendler 2008; Slavich and Cole 2013).…”
Section: Discussionsupporting
confidence: 78%
“…Most relevant for psychopathology research is the fact that several longitudinal studies have now shown that Val66Met genotype predicts risk for major depression following exposure to severe stressful life events, with Met carriers exhibiting a greater likelihood of developing depression following major life stress compared to their Val/Val counterparts (e.g., Aguilera et al 2009; Brown et al 2014; Wichers et al 2008). Although some contradictory results have been reported (e.g., Bresin et al 2013) and some evidence suggests that BDNF gene–environment interactions may be more pronounced for childhood than for adulthood life stress (Perea et al 2012), a recent meta-analytic review of 22 studies found that having a Met allele at the Val66Met locus is a reliable marker of risk for stress-induced depression (Hosang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to report this association in this setting although it is consistent with research indicating depression often develops in the context of multiple, cumulative stressful life events (Kendler et al . 1999; Brown et al . 2014; Swartz et al .…”
Section: Discussionmentioning
confidence: 99%
“…Quality assessment of brain-derived neurotrophic factor (BDNF), life stress and depression studies [43,[65][66][67][68][69][70][71][73][74][75][76][77][78][79][80][81][82][83]85,88,89].…”
Section: Additional Filementioning
confidence: 99%